O ensino de Artes em Parintins: diálogos entre a abordagem tradicional e os aspectos do método montessoriano no ensino fundamental - Costa, Lorena Tavares da (Brasil, 2022)
The objective of this work is to show how Art Teaching is applied in the traditional approach and in the Montessori method, from counterpoints between both, and also to show how aspects of the Montessori method were applied in a school that uses elements of the traditional method for the transmission of knowledge. With this, the concepts of each method were presented, as well as it’s representatives, using the experiences in PIBID, supervised internships I and II, other people's experiences and the author's personal experience to make analyses and, from these, the practice in the classroom. In the theoretical referential brings issues about art education, about the traditional method, Montessori and about the child. As a result, there was an opportunity and possibility to conduct a Montessori class and this observe how each teaching method works in practice.